Optimization of Pramipexole-Loaded In Situ Thermosensitive Intranasal Gel for Parkinson’s Disease - Rushi Trivedi; Vahid Vikram Minglani; Ahmed M. El-Gazzar; Gaber El-Saber Batiha; Mohamed H. Mahmoud; Mitesh Patel; Meenakshi Patel (Pharmaceuticals, 2024)
The objective of the present work was to develop and optimize an intranasal in situ gel of Pramipexole dihydrochloride for enhanced drug delivery, better patient acceptability, and possible proper treatment of Parkinson’s disease. Preliminary studies were performed to select formulation components and identify key variables affecting the formulation. The optimization of the in situ gelling system of Pramipexole dihydrochloride was achieved by applying 32 full factorial design using Design-Expert® software (Stat-Ease 9.0.6 version) and taking concentrations of Poloxamer 407 (X1) and HPMC K4M (X2) as independent variables. The gelling temperature, gel strength, and percentage of drug diffused after 8 h were taken as dependent variables. The software provided an optimized formulation, with 16.50% of X1 and 0.2% of X2 with the highest desirability. An in vivo drug retention time study was performed for the optimized formulation in Wistar rats. The results of the optimization process demonstrated that the selected gel formulation exhibited desirable characteristics, including gelation near body temperature, good gel strength, suitable viscosity, and sustained drug release. The optimized formulation displayed significantly higher drug retention, lasting about 5 h, versus the plain poloxamer gel formulation. Hence, it was concluded that the optimized formulation will remain affixed at the site of application for a significant time after intranasal administration and consequently sustain the release of the drug. The optimized formulation was found to be stable during the stability studies. The developed dosage form may improve patient compliance, enhance nasal drug residence, and offer sustained drug release. However, further clinical studies are necessary to validate these findings.